Analysis of Job Suitability with Automotive Engineering Educational Background of Vocational High School Graduates - Exaudi Ziliwu; M. Giatman; Ambiyar; Dedy Irfan (Jurnal Penelitian Pendidikan IPA, 2025)
Many Automotive Engineering vocational school graduates end up working outside their field due to pressing economic needs. They tend to choose available jobs rather than wait for jobs that match their skills. Their families' limited financial situation means they don't have the flexibility to wait for job openings in the automotive industry, especially if those jobs require additional skills they haven't yet mastered. This situation reflects the fact that economic factors are the primary driver of career decisions, even when those decisions are not aligned with one's educational background. To address this issue, various strategies can be implemented. One such strategy is strengthening relationships between schools and industry through link and match programs. This study aims to determine the extent to which automotive engineering competence and the type of job pursued influence the job relevance of vocational high school (SMK) automotive graduates. A quantitative approach was employed using a survey method, and the data were analyzed through simple and multiple regression analysis. The sample consisted of SMK Automotive Engineering graduates in Gunungsitoli who had entered the workforce in 2023–2024. The results showed a significant relationship between automotive engineering competence and the type of job pursued with the job relevance of graduates. Both independent variables made a substantial contribution to the alignment between job and educational background.